The rubber glove-allergen protein sensor :development of rubber glove allergy protein imprinted polymer for the use as a sensing element in quartz crystal microbalance and inter-digital conductometric sensor - Roongnapa Srichana (Prince of Songkla University, 2012)
National Research Council of Thailand